2018
DOI: 10.1007/s10545-018-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of enzyme replacement therapy for juvenile-onset Pompe disease: a systematic review

Abstract: Aim The objective of this research was to determine the effectiveness of enzyme replacement therapy for juvenile-onset Pompe disease (patients aged 2 to 18 years at symptom onset) by systematic review. Methods A systematic search was conducted according to a protocol designed a priori of bibliographic databases and search engines. Studies selected according to pre-specified criteria were assessed for quality and risk of bias using standardised appraisal tools. Data were reported according to PRISMA conventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
4
2
Order By: Relevance
“…Another noteworthy finding of our study was that there is no significant association between CHE and the QOL in patients with LOPD, which is inconsistent with studies conducted in the United States and Europe [ 54 , 55 ]. Although patients can have adverse infusion reactions, a systematic review of 21 international articles concluded that most adverse events were mild or moderate, and ERT is well tolerated in general [ 56 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another noteworthy finding of our study was that there is no significant association between CHE and the QOL in patients with LOPD, which is inconsistent with studies conducted in the United States and Europe [ 54 , 55 ]. Although patients can have adverse infusion reactions, a systematic review of 21 international articles concluded that most adverse events were mild or moderate, and ERT is well tolerated in general [ 56 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another noteworthy nding of our study was that CHE had no signi cant in uence on the QOL in patients with LOPD compared with other non-PD rare disease patients, which is inconsistent with studies conducted in the United States and Europe [45,46]. Although patients can have adverse infusion reactions, the expensive ERT has been highlighted in Western societies as a signi cant promoter of QOL, especially at the early stages of treatment [47].…”
Section: Discussioncontrasting
confidence: 81%
“…We decided to include also this endpoint because all together, 6-MWT, FVC, and muscle strength represent the first recommended functional assessment by the Swiss Guidelines of Pompe disease [31], in monitoring the patients, and are the same outcomes recommended by the European Pompe Consortium [12]. In the analysis, we included studies that evaluated the muscle strength using the MRC grading scale, the QMT and the QMFT, which are the most used tools to evaluate muscle strength in Europe [32] and they also were already used in previous reviews on patients with JOPD [13]. Additionally, we performed a meta-analysis to investigate the efficacy of ERT on muscle strength in patients with LOPD.…”
Section: Results In Contextmentioning
confidence: 99%
“…By the consensus meetings of the European Pompe Consortium, a systematic review with a narrative synthesis due to the expected heterogeneity was undertaken showing a beneficial effect of ERT at the group level but with varied treatment effects at the individual level [12]. For JOPD patients only, a systematic literature review without statistical synthesis due to a low quality of original articles suggested a short-term benefit from ERT through improved muscle strength and reduced need for assisted ventilation [13].…”
Section: Introductionmentioning
confidence: 99%